Global, regional, and national burden of nonrheumatic calcific aortic valve disease based on GBD study 2021 - Baiqiang Wang; Zeyuan Mei; Hong Yang; Wei Gao; Lianyue Ma; Guipeng An (Scientific Reports)
Abstract Calcific aortic valve disease (CAVD) is among the most prevalent forms of nonrheumatic valvular heart disease, imposing a substantial global health burden. This study examined CAVD trends to provide insights for the development of effective prevention strategies. Using Global Burden of Disease Study 2021 (GBD 2021) data, we analyzed the age-standardized prevalence, incidence, mortality, and disability-adjusted life years (DALYs) of CAVD, along with trends, age- and sex-specific patterns, contributing factors, and projections through 2036. From 1992 to 2021, the number of global CAVD cases rose from 4.97 to 13.32 million and the age-standardized prevalence rate (ASPR) increased from 130.82 to 158.35 per 100,000 people. While both the ASPR and age-standardized incidence rate (ASIR) steadily increased, the age-standardized mortality rate (ASMR) and age-standardized DALYs rate (ASDR) declined. The burden of CAVD progressively worsened with age. Males generally had higher prevalence and incidence rates compared with females. However, in individuals > 85 years, females exhibited significantly higher mortality and DALY burdens. The CAVD burden was positively correlated with the sociodemographic index (SDI); the correlation was stronger in High SDI regions compared with Low SDI regions, and this gap widened over the last three decades. Population growth and aging were the primary contributors to the increasing burden, while epidemiological transitions helped reduce the ASMR and ASDR in regions with a high SDI. By 2036, the ASPR, ASIR, ASMR, and ASDR of CAVD are projected to decline in the High and High-middle SDI regions. In contrast, the ASPR and ASIR are expected to continue to increase, whereas the ASMR and ASDR are anticipated to remain relatively stable in other SDI regions. Although significant progress has been made globally in the prevention and treatment of CAVD, the complex demographic and regional disparities underscore the need for targeted prevention and treatment strategies to further alleviate the burden and enhance patient outcomes.